Biochemical and crop responses of tea (Camellia sinensis) to applied nitrogen - S. MARIMUTHU; L. MANIVEL; R. RAJ KUMAR (Indian Journal of Agronomy, 2001)
Changes in nitrate-reductase enzyme activity in feeder roots and certain bio- chemical constituents of pluckable shoots in tea [Camellia sinensis (L.) 0. Kuntze] after fertilizer application were monitored at weekly intervals in the field-grown ma- ture bushes to determine the optimum N level and the interval between 2 applica- tions. Nitrate-reductase activity (NRA) built linearly up to 300 kg Nlhalyear, but de- clinedat 600 kg Nlha. Nitrogen at 600 kg!ha. though balanced with potash, inhibited NRA in feeder roots and increased the nitrogenous compounds in green shoots. The NRA was at peak during third week and declined in fourth week. For sustained effi- ciency and productivity without any adverse effect on quality, 300 kg Nlha balanced with potash applied at a minimum of 3-4 weeks interval appeared optimum.
Keywords: Tea; Nitrate-reductase activity; N; Productivity